PERANCANGAN APLIKASI WEB PORTAL WARGA UNTUK KELUHAN DAN DISKUSI MENGGUNAKAN METODE SCRUM - Steven; Saragih, Saut Pintubipar (LPPM Universitas Putera Batam, 2025)
Advances in information technology provide great opportunities to improve public services, especially in managing public complaints. In Perumahan Nusa Jaya, Kelurahan Sungai Panas, Batam City, which is a community with high social interaction, complaint management is currently still done manually through WhatsApp groups. This approach faces challenges, including lack of focused attention, difficulty tracking complaint status, limited documentation, and lack of transparency. Survey data revealed that most residents consider the current system ineffective and needs innovation. This study proposes the design of a citizen portal web application to streamline the management of complaints and community discussions. This system aims to record complaints periodically, track progress in resolution, provide organized documentation, and increase transparency and accountability for RT/RW administrators. This development follows the Scrum methodology, allows for iterative improvement, and uses the Unified Modeling Language (UML) for process modeling. The interface designed using Figma ensures a user-friendly experience. The proposed application will improve efficiency, transparency, and citizen satisfaction in managing public services in Perumahan Nusa Jaya. By integrating modern technology, this initiative is in line with sustainable development goals, which encourage better community-level governance.